Rural income and employment diversity in India during 1994 and 2005 - Shariff, Abusaleh (SAGE Publications, 2009)
This article assesses the structure of rural income and employment according to source in India. It probes the size and role of ‘rural nonfarm employment’ in poverty alleviation. Data from two nationally representative rural sample surveys (33230 and 27010 households respectively) with reference years 1993–1994 and 2004–2005 are subjected to multinomial logit and Censored Least Absolute Deviation Model (CLAD) regressions to explore importance of diversity of income sources across states and regions. These are rare data on direct household income estimates in the multi-model survey context having advantage of many household and village level determinants suitable for advanced analysis. Evidence suggests considerable income diversification over the reference decade, but distribution of shares suggests that top most quintile draw almost all of the benefits of recent economic growth in India. The economic linkage between the Rural Nonfarm Employment (RNFE) and rural wage rates has reduced and has been almost non existent during the later reference year in analysis.